(3TQM QSGdI GdSjO GdTQja GdLQLGfi aj BOGH GdHMKs - (3Gdehdi YHO GdcQje LdHis; (3GdSjO GdTQja GdLQLGfjs
(3ChdgG (B:s
(3GdMeO def dGeGfY dYWGFg hdG efGbV dbVGFg bGd SjO GdeMbbjf hTQja GdeObbjf EPG bdJ cdGekG cJH fGbdkG WdH GdSGFd UMJg s
(3BNQgG (B:s
(3hYf GdONd bHd Gdbge HGdJeGe hYjf eGdGjYfi HGdebUhO hYf GdVMc hQaY GdUhJ hYf Cf GdNUe MbjQkG hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B27s
(3GdfSNI HgG MhGTs
(3COHs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs